1999
DOI: 10.1042/0264-6021:3410193
|View full text |Cite
|
Sign up to set email alerts
|

Processing of normal lysosomal and mutant N-acetylgalactosamine 4-sulphatase: BiP (immunoglobulin heavy-chain binding protein) may interact with critical protein contact sites

Abstract: The lysosomal hydrolase N-acetylgalactosamine-4-sulphatase (4-sulphatase) is essential for the sequential degradation of the glycosaminoglycans, dermatan and chondroitin sulphate and, when deficient, causes the lysosomal storage disorder mucopolysaccharidosis type VI. The cysteine at codon 91 of human 4-sulphatase was identified previously as a key residue in the active site of the enzyme and was mutated by site-directed mutagenesis to produce a 4-sulphatase in which cysteine-91 was replaced by a threonine res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The main parameter for the evaluation of affinity for BiP was the ability of a given peptide to stimulate in vitro the ATPase activity of the chaperone. In immunoglobulin heavy and light chains (Knarr et al, 1995;Augustine et al, 2001), in gp160 (Knarr et al, 1999), and in the lysosomal hydrolase N -acetylglucosamine-4-sulfatase (Bradford et al, 1999), most of the predicted potential sites of BiP binding involve interdomain or subunit contact sites or hydrophobic residues that are buried within the folded protein, as revealed by crystallography. However, at present, there is scarce evidence regarding whether these predictions apply to in vivo situations: direct information on sequences recognized in vivo on real proteins, in any eukaryotic system, is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…The main parameter for the evaluation of affinity for BiP was the ability of a given peptide to stimulate in vitro the ATPase activity of the chaperone. In immunoglobulin heavy and light chains (Knarr et al, 1995;Augustine et al, 2001), in gp160 (Knarr et al, 1999), and in the lysosomal hydrolase N -acetylglucosamine-4-sulfatase (Bradford et al, 1999), most of the predicted potential sites of BiP binding involve interdomain or subunit contact sites or hydrophobic residues that are buried within the folded protein, as revealed by crystallography. However, at present, there is scarce evidence regarding whether these predictions apply to in vivo situations: direct information on sequences recognized in vivo on real proteins, in any eukaryotic system, is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed in MSD fibroblasts showed that arylsulfatase A, arylsulfatase B and steroid sulfatase, although inactive, were normally processed [23]; results obtained from expression studies on the cysteine 84 mutant of iduronate sulfatase [20] showed that a C84A mutation had a drastic effect on processing, while C84T replacement produced a small amount of IDS inactive mature forms. Experiments performed on the cysteine 91 of N ‐acetylgalactosamine 4‐sulfatase showed that the C91T replacement caused a lower level of intracellular protein [19]; however, a subsequent study revealed that the C91T was synthesized normally in the RER where it was apparently retained and degraded by the quality control system, but was not processed [24]. Also in this study, since RT‐PCR analysis showed that the C70M mutant was correctly translated in vitro, the C70M protein seems to be synthesized but not proteolytically processed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that point mutations may directly affect the protein function or alter the correct folding and cause subsequent premature degradation of the mutant proteins within the RER; the resulting protein misfolding has been implicated in the pathogenesis of some genetic diseases [25,26]. The mechanism involved in the degradation of the mutant protein in lysosomal storage disorders has yet to be fully characterized, but recent evidence indicates the involvement of the degradation system in the RER quality control processes [24]; furthermore, protein conformation changes have been observed in the mutant 4‐sulfatase protein in patient fibroblasts [19].…”
Section: Discussionmentioning
confidence: 99%
“…We performed BiP‐binding predictions on the FNR TP using a program based on a mathematical algorithm previously reported (Blond‐Elguindi et al 1993). The algorithm has been successfully used to predict the presence of BiP‐binding sequences in several polypeptides such as the light and heavy chains of antibodies (Knarr et al 1995), the precursor of the HIV type I envelope glycoprotein (gp 160) (Knarr et al 1999) and along the primary sequence of the lysosomal 4‐sulfatase (Bradford et al 1999). In a previous work we analyzed in depth the interaction of the E. coli Hsp70 DnaK with the TP of preFNR.…”
Section: Discussionmentioning
confidence: 99%